The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/echo.13742
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the area and shunt volume of multiple, circular, and noncircular ventricular septal defects: A 2D/3D echocardiography comparison and real time 3D color Doppler feasibility determination study

Abstract: Background Quantification of defect size and shunt flow is an important aspect of ventricular septal defect (VSD) evaluation. This study compared three‐dimensional echocardiography (3DE) with the current clinical standard two‐dimensional echocardiography (2DE) for quantifying defect area and tested the feasibility of real time 3D color Doppler echocardiography (RT3D‐CDE) for quantifying shunt volume of irregular shaped and multiple VSDs. Methods Latex balloons were sutured into the ventricles of 32 freshly har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Our results also confirmed the importance of health education regarding the safety and efficacy of transthoracic device closure of VSD. Studies have shown that heart models created using 3D printing technology are useful for CHD education [20][21][22]. Such models inspired students' interest in learning about CHD and improved the effectiveness of medical education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also confirmed the importance of health education regarding the safety and efficacy of transthoracic device closure of VSD. Studies have shown that heart models created using 3D printing technology are useful for CHD education [20][21][22]. Such models inspired students' interest in learning about CHD and improved the effectiveness of medical education.…”
Section: Discussionmentioning
confidence: 99%
“…Such models inspired students' interest in learning about CHD and improved the effectiveness of medical education. The 3D-printed heart models can represent real spatial relationships and permit the physical manipulation of external and intracardiac structures [20][21][22]. Therefore, we could use a heart model to make descriptions of this procedure more concrete, which would make parents would be more receptive to information about the procedure and more easily accepted it.…”
Section: Discussionmentioning
confidence: 99%
“…Many analysts now argue that the strategy of 3DTTE/3DTEE over 2DTTE has been successful for the evaluation of VSD following AMI, for example, argues that VSD shape and its changes during the cardiac cycle can be visually and quantitatively displayed. 3DTTE/3DTEE may thus be particularly useful before and during percutaneous VSD closure [27][28][29] .…”
Section: Spontaneous Pivsd Closurementioning
confidence: 99%
“…Nevertheless, it is difficult to obtain a uniform standard due to empirical judgment with the naked eye. Recent evidence demonstrated that three-dimensional color Doppler echocardiography is a feasible method for quantifying the shunt volume in VSD patients [27] , which had potential value on judging the indication of residual shunt need a secondary percutaneous procedure or surgical intervention. In order to reduce the occurrence of adverse events and complications, there is no doubt that the physicians should take care and comprehensive into consideration the medical conditions of patients to assess which is the best therapeutic decision.…”
Section: Adverse Events and Complicationsmentioning
confidence: 99%
“…Nitrogen-containing heterocyclic compounds have a diverse range of biological and pharmacological properties [1][2][3][4]. Thiazolo [3,2a]pyridines, containing two fused heterocyclic rings, also; it's found in medicinal chemistry as they have an excellent biological activity with a wide range of applications, including antimicrobial [5], antiviral [6] antihypertensive [7], antihistaminic [8], neurotropic [9], anticonvulsant [10], antidepressant, sedative, analgesic [11,12] and anti-cancer activities. Among the various of anthraquinones are identified also biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%